Evaluating K13 and Merdeka Curriculum Implementation in Primary Education: A Comprehensive Literature Review - Pratiwi, Agustin Adelia Sisca; Elizar; Apriza, Berta; Sumarno (Universitas Pendidikan Ganesha, 2024)
Elementary education in Indonesia has undergone significant reforms with the introduction of the K13 Curriculum and the Merdeka Curriculum. These changes aim to enhance the quality of education and equip students with 21st-century skills. This study seeks to analyze the differences in the implementation of the Merdeka Curriculum and the K13 Curriculum through a systematic literature review. The research employed the SLR (Systematic Literature Review) method using Google Scholar as the primary database. The literature reviewed was limited to the period from 2019 to 2023, using a three-stage keyword search process. The first stage resulted in 3,340 documents with the keyword